2022
DOI: 10.3390/nu14091747
|View full text |Cite
|
Sign up to set email alerts
|

The Administration of Panax Ginseng Berry Extract Attenuates High-Fat-Diet-Induced Sarcopenic Obesity in C57BL/6 Mice

Abstract: Sarcopenia and obesity are serious health problems that are highly related to several metabolic diseases. Sarcopenic obesity, a combined state of sarcopenia and obesity, results in higher risks of metabolic diseases and even mortality than sarcopenia or obesity alone. Therefore, the development of therapeutic agents for sarcopenic obesity is crucial. C57BL/6 mice were fed with a high-fat diet (HFD) for 9 weeks. Then, mice were administered with Panax ginseng berry extract (GBE) for an additional 4 weeks, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Deactivation of the PI3K/Akt pathway inhibits protein synthesis and promotes protein degradation. It causes an imbalance in muscle mass maintenance and induces muscle loss [34]. An essential surveillance mechanism targeting defective and harmful mitochondria to degradation is the selective form of autophagy called mitophagy [35].…”
Section: Discussionmentioning
confidence: 99%
“…Deactivation of the PI3K/Akt pathway inhibits protein synthesis and promotes protein degradation. It causes an imbalance in muscle mass maintenance and induces muscle loss [34]. An essential surveillance mechanism targeting defective and harmful mitochondria to degradation is the selective form of autophagy called mitophagy [35].…”
Section: Discussionmentioning
confidence: 99%
“…For sarcopenic obesity induction, mice were randomly divided into two groups: a normal diet-fed group (CON; n = 10) and a high-fat diet-fed group (HF; n = 20). The HF group was fed a 60% kcal high-fat diet (D12492; Research Diets, New Brunswick, NJ, USA), and the ND group was fed a 10% kcal fat control diet (D12450J; matching sucrose to D12492, Research Diets, New Brunswick, NJ, USA) for 8 weeks [ 30 , 31 ], provided ad libitum. After sarcopenic obesity induction, the HF group was randomly divided into two groups: non-exercise high-fat diet-fed group (OB; n = 10) and exercise high-fat diet-fed group (EX; n = 10).…”
Section: Methodsmentioning
confidence: 99%
“…[93][94][95][96] Apart from clinical observations, some basic experiments have also shown that bioactive supplements such as whey peptide, omega-3 fatty acids, Panax ginseng berry and resveratrol could reduce fat volume, increase lean volume, and improve lipid metabolism and the energy cycle. [97][98][99][100] Although progress has been made in the study of functional supplements, their mechanism of action on sarcopenic obesity still needs to be further explored.…”
Section: Functional Supplementationmentioning
confidence: 99%